The Cambridge Companion to Literature and Food - Coghlan, J. Michelle (Singapore : Cambridge University Press, 2020)
"From feasts to fashion, awareness of the medieval quotidian has proven vital to interpreting its literature. Authors and audiences may yearn for transcendence, only to find it rooted to the social world of practice. As Jill Mann reminds us in 1979, a time when patristic, theologically grounded schools of criticism seemed predominant: "The material world is not merely a vehicle for expressing the immaterial, but on the contrary contains the heart of its meaning and its mystery." Allegory is bound inextricably to its literal level. Without a text there is no meaning to be hidden, these signifiers derived from everyday practice. Circumstances of existence-material details, everyday life-pervade author, text, and audience alike, and these are crucial to bridging the interpretive gap between then and now"--
Introduction: The literature of food / J. Michelle Coghlan -- Medieval feasts / Aaron K. Hostetter -- The art of early modern cookery / Joe Moshenska -- The romantic revolution in taste / Denise Gigante -- The matter of early American taste / Lauren Klein -- The culinary landscape of Victorian literature / Kate Thomas -- Modernism & gastronomy / Allison Carruth -- Cold War cooking / J. Michelle Coghlan -- Farm horror in the twentieth century / Michael Newbury -- Queering the cookbook / Katharina Vester -- Guilty pleasures in children's literature / Catherine Keyser -- Postcolonial tastes / Parama Roy -- Black power in the kitchen / Erica Fretwell -- A farmworker activism / Sarah D. Wald -- Digesting Asian America / Anne Anlin Cheng -- Postcolonial foodways in contemporary African literature / Jonathan Bishop Highfield -- Blogging food, performing gender / Emily Contois.
Keywords: Food in Literature